BD1-biased BET inhibition attenuates TXNIP-associated inflammation in diabetic MASH - Rabab S. Hamad; Sameh Saber; Elsayed A. Elmorsy; Maha M. Amer; Mohamed A.M. Ali; Hanan Eissa; Alshaimaa A. Farrag; Norhan Ahmed AbuoHashish; Shereen hamed; Mahmoud A. Abdelaziz; Adel I. Alalawy; Alaa Muqbil Alsirhani; et al. (Tissue and Cell, 2027)

Innovative use of Barley Straw to control algal blooms and improve wastewater quality: Microbial community insights in a sustainable pre-filtration conditioning - Atef Mohamed Gad Mohamed; Ashraf Ahmed; Eman A. Mahmoud; Eman M. Farahat; Khaled N.M. Elsayed; Abeer El Shahawy (Ecological Engineering, 2026)

The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

Enhanced mitigation of diabetic myocardial injury in rats via modulating the adiponectin/IRS-1/PI3K/p-AKT/FOXO-1 signaling by combining methotrexate and insulin - Mohamed S. Elsayed; Mahmoud Elshal; Manar G. Helal; Tarek Ibrahim (Molecular Biology Reports, 2026)

Temporal germination of lettuce under salinity and nano-silicon: A high-throughput phenomics framework with deep learning - Mohamed Ahmed Moustafa; Min Kang; Xiuqing Fu; Luxu Tian; Hanghang Li; Penghong Shen; Ziyi Zhang; Jianzhe Zhou; ChenXu Zhu; Junxiang Cheng; Sanglu Yang; Ahmed Elsayed Mahmoud Fodah; et al. (Plant Science, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

A comparative study on in-situ and ex-situ microwave catalytic co-pyrolysis for phenolic bio-oil production through machine learning and response surface methodology - Ahmed Elsayed Mahmoud Fodah; Ahmed Mahmoud Ahmed; Xiayu Liu; Juping Liu; Suzan A. Swalim; Taha Abdelfattah Mohammed Abdelwahab; Peixuan Xue; Jingai Shao; Xianhua Wang; Haiping Yang (Bioresource Technology, 2026)

Dietary yeast-derived nucleotides enhance reproductive efficiency, blood metabolic profile, antioxidant status, and immune function in rabbit does - Noura H. Gouda; Sameh A. Abdelnour; Elsayed S. I. Mohammed; Mohamed Shawky El Sayed; Mohamed Ashour; Roshmon Thomas Mathew; Mohammed Tariq Saud Albaloushi; Hailah M. Almohaimeed; Ehab El-Haroun; Mahmoud S. Abd-Allah (Veterinary Research Communications, 2026)

Efficacy and safety of baxdrostat add-on in uncontrolled and resistant hypertension: a systematic review and meta-analysis of randomized controlled trials with GRADE certainty-of-evidence assessment - Mahmoud Elsayed; Yousr Ahmed; Abdelrahman M. Elettreby; Mohammed A. Elbahloul; Mohamed A. Alsaied; Nada Mutiq Alshahrani; Dina M. Khodeer; Mohamed Shaltout; Alshaimaa Shaltoot; Mohammed Eldakrory; Ahmed Elsharif; Aladin Altic; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Combined Bacillus Amyloliquefaciens and Bacillus Licheniformis for Preventive Health Management: Effects on Growth Performance, Intestinal Integrity, and Oxidative Status in Broilers Under Controlled Housing - Ahmed Ali Saleh; Mahmoud M. Aboud; Neamat Badwi; Mohammed A. Kamal; Elsayed Osman Hussein; Branislav Galik; Hana Hakami; Ahmed Sami; Abeer A. Kirrella (Probiotics and Antimicrobial Proteins, 2026)

Mitigating the impact of salinity and/or bisphenol A stress on the performance of the tomato crop by spraying with an algal extract of Ascophyllum nodosum L. - Mahmoud S. Abdelmoneim; Mohamed A. Ghazy; Elsayed E. Hafez; Sherif F. Hammad; Mona F.A. Dawood (Journal of Hazardous Materials, 2026)

Culturomics of the plant microbiota: the emerging in situ similis cultivation strategies to meet the complexity of nutritional requirements of microbiota associated with plants of multiple species, growth stages and compartments - Nabil A. Hegazi; Sascha Patz; Florian Fricke; Ayatollah S. El-Zayat; Marwa N. Ahmed; Mervat A. Hamza; Nada A. Moner; Randa M. Abdel-Fatah; Eman H. Nour; Tarek R. Elsayed; Mahmoud S. Abdelwahab; Omar M. Shahat; et al. (Plant and Soil, 2026)
Background The holobiont" refers to the plant and its associated microbiota that are pivotal to the plant's health, fitness, and survival. By in vitro culturing and functionally characterizing members of the plant microbiota, their specific roles in influencing plant responses to environmental changes can be determined and manipulated to foster sustainable agriculture and ecosystem management. Aims The review presents a comprehensive survey and current updates on culturomics of plant microbiota within the overall context of: a) the importance of understanding the plant holobiont composition and functioning; b) the necessity to in vitro track down and explore environmental microbiomes, entailing the plant microbiome with its myriad composition and spatio-temporal dynamics and mobility in various plant species, compartments and growth stages and c) the recent developments of the emerging in-situ similis cultivation strategies grounded on plant-based culture media. Conclusions The review highlights the urgent need to explore in vitro cultivation strategies built on compatible plant-based culture media, and the transformative role of omics technologies in refining these strategies. By bridging fundamental research and cultivation-based applications, such tools offer a gateway towards more sustainable and efficient in vitro cultivation systems, leading to a deeper understanding and potential manipulation of the plant holobiont.

In vitro domestication of halophyte microbiota for future SynCom application - Nada A. Moner; Tarek R. Elsayed; Wafaa M. Amer; Mervat A. Hamza; Hanan H. Youssef; Randa M. Abdel-Fatah; Mahmoud S. Abdelwahab; Omar M. Shahat; Gehan H. Youssef; Mahmoud El-Tahan; Mohamed Fayez; Florian Fricke; et al. (Plant and Soil, 2026)
Background and aims Microbiome-mediated strategies for future stressed-agriculture entail exploration of repertoires of halophyte microbiota. Culturomics strategies are advanced to improve culturability and extend diversity of microbiota of Salicornia europaea L. Methods The plant broth-based-seawater-culture medium (PBSW) was advanced for in vitro domestication of microbiota of endo-rhizosphere/endo-phyllosphere of S. europaea . Populations (Colony Forming Units, CFUs) and biomass production (Optical Density, OD) were monitored throughout successive steps of in vitro cultivation/domestication in liquid batch cultures. Culture-dependent methods were applied to cultivate and identify (16S rRNA gene sequencing) representative isolates; and culture-independent analyses (DGGE/qPCR) for community composition. Results PBSW supported higher CFUs counts; and related to 16S rRNA gene copy numbers (qPCR), increased (> 40 fold) culturability compared to NaCl-salted-standard culture medium. Successive in vitro domestication/batch cultures boosted bacterial growth, diminished differences among tested culture media and shortened doubling times (DT). PCR-DGGE showed divergence in culturable community composition primarily attributed to culture media. 16S rRNA gene sequencing of representative isolates indicated: a) greater diversity in endo-phyllosphere than endo-rhizosphere; b) abundant phyla were Pseudomonadota/Bacillota /Actinomycetota; c) dominance of Halomonas among 15 genera identified; d) Gracilibacillus, Metabacillus, Mixta, Salinicoccus, Zhihengliuella, Marinobacter, Marinimicrobium and Planomicrobium were first reported/cultivated for S. europaea . In vitro domestication resulted in dominance of genera of Pseudomonadota/Bacillota for endo-phyllosphere and Halomona s sp. of Pseudomonadota for endo-rhizosphere. Conclusion PBSW created in situ similis milieu for cultivation of halophyte bacteria, and enabled in vitro domestication for propagating microbiota, instead of laborious construction of consortia of single isolates, for future SynCom applications.

In situ similis culturomic strategies based on vegetable (veggie)-discs extend diversity of in vitro-cultivated microbiota of vegetables - Randa M. Abdel-Fatah; Nada A. Moner; Eman H. Nour; Tarek R. Elsayed; Mohamed T. Abbas; Mahmoud S. Abdelwahab; Mervat A. Hamza; Hanan H. Youssef; Ahmed S. Shehata; Omar M. Shahat; Mohamed Fayez; Silke Ruppel; et al. (Plant and Soil, 2026)

Impact of nano-selenium supplementation on in vitro gas production, methane mitigation, and in vivo performance of Ossimi Egyptian Sheep - Hamdy Mohamed Khattab; Ahmed Zaki El-Basiony; Salwa Mahmoud Hamdy; Mahmoud Hassan; Nasr Elsayed El-Bordeny; Osama Mohamed Darwesh; Gamal Ali Elsayaad; Raafat Mahmoud Mohamed Gomaa (Tropical Animal Health and Production, 2026)

Optimizing Domestic Wastewater Treatment Using Moringa Oleifera Lam. Vegetated Constructed Wetlands: A Case Study et al.-Habil Wastewater Treatment Plant, Luxor - Naira Meky; Raouf Hassan; Mohamed F. Soliman; Aml Mahmoud; Mahmoud Elsayed (Water, Air, & Soil Pollution, 2026)

Trientine ameliorates bleomycin-induced pulmonary fibrosis in rats through copper chelation and modulation of the CTR1/LOX/COL pathway - Ibrahim T. Khalil; Mahmoud Elshal; Norhan M. Elsayed; Asmaa Radwan (Inflammopharmacology, 2026)
Pulmonary fibrosis (PF) remains a devastating disease. Copper (Cu), an essential trace element, has been implicated in fibrotic processes in various organs, including the lungs. This study investigated the potential protective effects of trientine (TRI), a copper chelator, against bleomycin (BLM)-induced PF in rats and explored the underlying mechanisms. PF was induced by intratracheal administration of BLM (5 mg/kg). Rats were randomly allocated into seven groups: normal control, TRI alone, BLM control, and four BLM plus TRI prophylactic or therapeutic groups receiving low (55 mg/kg) or high (110 mg/kg) TRI doses orally. Results demonstrated that TRI dramatically reversed BLM-elevated serum levels of lactate dehydrogenase and alkaline phosphatase, markers of tissue damage. The protective effects of TRI were multifaceted: it exhibited potent antifibrotic activity by reducing collagen buildup and inhibiting TGF-β, CTR1, LOX, and COL1 expression; it acted as an antioxidant by increasing antioxidant status and significantly upregulating Nrf2; and it served as an anti-inflammatory agent by decreasing inflammatory cytokines (TNF-α and IL-6) and modulating the NF-κB pathway by increasing NF-κB expression while limiting its activation and nuclear translocation, thereby reducing inflammatory signaling. Histopathological and immunohistochemical analyses confirmed substantial attenuation of collagen deposition and structural lung damage. Overall, TRI demonstrated potent antifibrotic, antioxidant, and anti-inflammatory properties, effectively protecting lung tissue against BLM-induced injury. These findings highlight copper chelation as a promising therapeutic strategy for pulmonary fibrosis and warrant further investigation into TRI’s clinical potential.

Sustainable management of olive trees under saline irrigation and soil conditions using micro-irrigation systems and remote sensing - Mohamed M. Mahmoud; Mohamed E. Abuarab; Ayman Shaban; Ibrahim Hmmam; Asmaa Gamal Abd El-hamied; Amr Mossad; Ali Mokhtar; Elsayed Youssief Ghoniem (Irrigation Science, 2026)
The study was carried out to examine the sustainable management of irrigation water for olive cultivation in sandy soils with varying levels of water salinity at a farm situated in the Regwa region of EL-Beheira Governorate, Egypt, which is noted for its arid climate, aiming to improve the effective utilization of sustainable ecosystems while optimizing economic returns for agricultural producers. Field experiments were implemented over two successive growing seasons, specifically 2022–2023 and 2023–2024, employing seven distinct irrigation methodologies: micro-sprinklers, T-tape GR drippers, Root Zone Watering System (RZWS), inline drippers, inline PC drippers, mist sprayers, and bubblers. In the 2022–2023 season, the inline dripper treatment yielded the highest output of 13.78 ton ha −1 , followed by the inline PC dripper and micro-sprinkler systems, which yielded 13.20 ton ha −1 and 12.45 ton ha −1 , respectively. In contrast, the mist sprayer treatment produced the lowest yield at 7.61 ton ha −1 . The oil content in olive fruits reached optimal levels under bubbler and inline PC dripper treatments in the second growing season at 40.0% and 39.87%, respectively. Conversely, the minimum oil content was recorded under micro-sprinkler and inline dripper treatments in the first growing season, yielding 34.31% and 34.36%, respectively. During the first growing season, the inline dripper exhibited irrigation water productivities (IWPs) of 31.60 kg m −3 , followed by the inline PC dripper with an IWP of 30.28 kg m −3 . In stark contrast, the mist sprayer reported the lowest IWPs of 0.74 kg m −3 in the second growing season. The distribution patterns of soil moisture and salinity within the root zone were analyzed utilizing Surfer software. The most significant net farm income (NFI) was attained under the inline PC dripper treatment, with an NFI of 38,664.35 US$ y −1 , succeeded by the inline dripper and micro-sprinkler treatments with NFIs of 36,010.95 and 30,265.94 US$ y −1 , respectively; the mist sprayer demonstrated the lowest NFI at 17,186.49 US$ y −1 .

Synchronous natural infection of Nile tilapia (Oreochromis niloticus) by drug-resistant Pseudomonas aeruginosa and Saprolegnia parasitica: insights into water quality, phenotypic traits, and genotypic profiles - Reham M. El‑Tarabili; Mahmoud E. Elsayed; Hanan S. Khalefa; Hanan Elghayaty; Zainab Mohamed El Kattawy; Mohamed Marzok; Sherief M. Abdel-Raheem; Hesham L. Ismail; Dalia A. Abdel-moneam (Veterinary Research Communications, 2026)

Maternal high-fat diet and its multigenerational impact on hypertension and metabolic alterations in Wistar rat offspring - Maghawry Hegazy; Mahmoud Mohamed Mokhtar; Elsayed G. E. Elsakka; Hesham A. El-Mahdy; Samy Y. Elkhawaga; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed Aglan; Ahmed M. Mansour; Salama Abdo Salama; Hamada Ahmed Mokhlis; Hesham Fathy Hassan; et al. (Journal of Molecular Histology, 2026)

Comparative study of obeticholic acid and rosuvastatin in high-fat/fructose diet–induced metabolic dysfunction: role of AMPK, PPAR-γ, SREBP-1c, and STAT3 pathways - Sahar M. Elashmony; Yosra Alhindi; Dina H. Merzeban; Rehab A. Mohammed; Asmaa Mohamed Elsayed; Mariham George Loqa; Rania H. Mahmoud; Hanan A. Shamardl; Mona Farag Shabana (Journal of Molecular Histology, 2026)

A self-organized fuzzy neural model for the pressurizer system in nuclear power plants - Elsayed H. Ali; Amal A. Sheta; Sayed M. El-Araby; Mohammed I. Mahmoud; Tarek A. Mahmoud (Annals of Nuclear Energy, 2026)

Arbuscular mycorrhizal fungi confers resistance to Macrophomina phaseolina in coriander under different nitrogen fertilizer rates - Marzouk R. Abdel-Latif; Abdelrazek S. Abdelrhim; Ranya M. S. El-Ashmony; Yasmin M. R. Abdellatif; Hanaa A. H. Armanious; Ismail A. A. Tantawy; Mahmoud Elsayed; Abeer S. Alqurashi; Hatim M. Al-Yasi; Esmat F. Ali; Abdelmonim Ali Ahmad (Journal of Plant Pathology, 2026)

Zero Liquid Discharge Performance in Complex Fertilizer Industry Wastewater Treatment - Mahmoud Elsayed; Abdelrahim M. Abdeldaim; Mohamed F. Soliman; Raouf Hassan; Naira Meky (Water, Air, & Soil Pollution, 2026)

Exploitation of Sentinel-2 Spectral Bands and Vegetation Indices in Potato Yield Estimation - Mohamed E. S. Amin; Mohsen Nabil; Mahmoud. A. Abdelfattah; Elsayed. S. Mohamed; Ali G. Mahmoud (Journal of the Indian Society of Remote Sensing, 2026)

Evaluation of golden ipecac extract for enhancing the functional properties and stability of food products - Mahmoud Elsayed; Reham M. Kamel; Asmaa Shafiq; Mohamed Abdelbaset Salama; Samar M.S. Shawir (Food and Humanity, 2025)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

Exploring the Efficacy and Safety of Argatroban as an Adjunct to Antiplatelet Therapy in Ischemic Stroke Patients: A Systematic Review and Meta-analysis - Yousr Ahmed; Mostafa Hossam El Din Moawad; Gulnaz Bahtiyarova; Younes Nabgouri; Mohammed Elkholy; Reham M. Wagih; Ibrahim Serag; Ibraheem M. Alkhawaldeh; Mohamed Abouzid; Mahmoud Elsayed (Translational Stroke Research, 2025)

Chrysin-loaded poly (lactic-co-glycolic acid) nanoparticles alleviate sepsis-induced splenic injury by regulating myeloid-derived suppressor cells - Islam Ahmed Abdelmawgood; Abeer Mahmoud Badr; Asmaa Elsayed Abdelkader; Noha A. Mahana; Ayman Saber Mohamed; Hadeer Hesham Abdelfattah (Immunologic Research, 2025)

Impact of Effective Probiotic Microorganisms (EPMs) on Growth Performance, Hematobiochemical Panel, Immuno-Antioxidant Status, and Gut Cultivable Microbiota in Striped Catfish (Pangasianodon hypophthalmus) - Mahmoud Abdullah Elnakeeb; Ahmed Mohamed Ashry; Ahmed Mohamed El-Zayat; Abdel Wahab Abdel-Moez Abdel-Warith; Mahmoud Mohamed Habiba; Elsayed Mohamed Ibrahim Younis; Simon John Davies; Ibrahim Mohamed Ibrahim; Fatma Elzhraa; Ahmed Mohammed El-Sebaey (Fishes, 2025)
Striped catfish, Pangasianodon hypophthalmus, has recently emerged as a promising candidate for Egyptian aquaculture owing to its rapid growth; however, under intensive culture, it is vulnerable to Aeromonas hydrophila. The efficacy of dietary supplementation with effective probiotic microorganisms (EPMs) in enhancing growth performance, feed utilization, physiological health, and disease resistance of P. hypophthalmus against A. hydrophila challenge was evaluated. A 90-day feeding trial was conducted with 300 fish randomly distributed into four triplicate groups (25 fish per replicate) reared in 12 indoor fiberglass tanks: a control and three groups receiving EPMs at inclusion levels of 1.5%, 3%, and 4.5%. The results showed significant, dose-dependent improvements across all EPMs-supplemented groups in survival, growth rates, feed utilization, and hematological parameters (RBC, Hb, PCV, WBC, and lymphocytes). Dietary EPMs led to significant improvements (p ≤ 0.001) in digestive efficiency, protein and lipid metabolism, antioxidant enzyme activity, immune performance, and the ability of striped catfish to withstand A. hydrophila infection. Hepatobiliary enzyme activities (ALT, AST, and ALKP), glucose levels, lipid profile markers, and hepatic MDA exhibited a significant linear decrease (p ≤ 0.0001) with increasing EPMs levels. The gut microbial composition showed a dose-dependent increase in beneficial lactic acid bacteria (LAB) and a reduction in TAPC, pathogenic coliforms (TFCC), and Vibrio spp. (TVC). These results demonstrate the dose-dependent effects of EPMs on enhancing aquafeed efficiency, overall health, and innate immunity in striped catfish.

Experimental test on a slender masonry wall with an alternative reinforcement configuration - Rafael Gonzalez; Alan Alonso; Mahmoud Elsayed; Carlos Cruz-Noguez; Douglas Tomlinson (Engineering Structures, 2025)

Sustainable valorization of agro-waste by microwave pyrolysis: mechanisms, optimization, catalyst pathways, integration strategies, and perspectives - Ahmed Elsayed Mahmoud Fodah; Haiping Yang; Xianhua Wang; Ziyue Tang; Rizk Rabea Kamel Elbessoumy; Mohamed Ahmed Shetawy; Elwan Ali Darwish; Taha Abdelfattah Mohammed Abdelwahab (Bioresource Technology, 2025)

Cardioprotective effects of ghrelin and Wharton’s jelly-derived mesenchymal stem cells, alone and in combination, in doxorubicin-induced myocardial injury in rats - Amy F. Boushra; Christina Sabry Yacoub; Hamed Mohamed Osman; Amani M. El Amin Ali; Azza Mohamed Elamir; Asmaa Mohamed Elsayed; Sarah Mahmoud Gamal (Journal of Molecular Histology, 2025)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

Dietary spirulina platensis a promising growth promotor and immune stimulant in broiler chickens - Enas Mahmoud; Gehad Elsayed; Azza Hassan; Ahmed Ateya; Shimaa Abd El-Salam El-Sayed (Natural Product Research, 2025)

Comparison between clopidogrel and ticagrelor in CYP2C19 loss-of-function alleles coronary artery disease and stroke patients: a meta-analysis - Mahmoud Elsayed; Mostafa Hossam El Din Moawad; Mohammed Elkholy; Yousr Ahmed; Younes Nabgouri; Gulnaz Bahtiyarova; Ibraheem M. Alkhawaldeh; Mohamed Abouzid; Reham M. Wagih (European Journal of Clinical Pharmacology, 2025)

Assessment and analysis of carbon footprint trends at AASTMT main campus (2018–2021): an approach toward a net-zero future - Wafaa Elsayed; Mohamed Abousena; Mohamed Shaltout; Mahmoud Elbawab; Kareem Tonbol (Euro-Mediterranean Journal for Environmental Integration, 2025)

Protective effect of valsartan alone and in combination with neprilysin inhibitor (valsartan + sacubitril) against hepatic ischemia–reperfusion injury: targeting angiotensin II receptor-neprilysin and modulating SMAD-4/NF-κβ/JNK pathways in rats - Deiaa E. Elsayed Abouzed; Duaa Abdullah Bafail; Shereen Mahmoud Refaie; Moustafa O. Aboelez; Asmaa A. Elsayed; L. O. Mallasiy; Nervana M. K. Bayoumy; Hanan Hagar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The impact of betalains and organic selenium on the physiological responses, blood metabolites, redox status, and semen quality of heat-stressed rabbits - Tharwat A. Imbabi; Eman H. Halawa; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Dina A. Selim; Mohamed H. Abdel Aal; Lamiaa M.M. EL-Maghraby; Abdalla El-Hadary; Shimaa A. Amer; Simon J. Davies; Mohamed S. Basiouny; Mahmoud Sitohy; et al. (Animal Feed Science and Technology, 2025)

Evaluation of the Qawasim Formation through integration of available data from El Basant wells, Nile Delta, Egypt - Ahmed Sedki; Mohamed Abd Elkhalek Mahmoud Abdelhady; Hany Elsayed Ahmed; Mohamed Reda (Arabian Journal of Geosciences, 2025)

Enhancing flexural performance of rubberized concrete beams through incorporation of rice husk ash as cement replacement - Noha Hussein; Mohamed Abou Elmaaty; Mansour Alturki; Mahmoud Elsayed (Engineering Structures, 2025)

A Prospective Approach for Screening of Potential Evolution of Aflatoxins in Fish and Fish Feed: Molecular and Afla Fluorometry Assays - Nada H. Eidaroos; Abdelazeem M. Algammal; Mahmoud Mabrok; Mamdouh Y. Elgendy; Mahmoud E. Elsayed; Eman M. El-Diasty; Sara M. El-khamisy; Reham M. El-Tarabili (Current Microbiology, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Adaptation and development plans of the Egyptian ports under the impacts of climate change - Ahmed A. Romya; Ahmed Elsayed Elkut; Asmaa A. Abu Zed; Hossam M. Moghazy; Maysara Khairy El-Tahhan; Akram Soliman; Mona G. Ibrahim; Moheb Iskander; Mahmoud Sharaan (Ocean & Coastal Management, 2025)

Omega-3 supplementation in migraine prophylaxis: An updated systematic review and meta-analysis - Haneen Sabet; Abdallah Abbas; Ibraheem M alkhawaldeh; Shrouk Ramadan; Moaz Elsayed Abouelmagd; Ebrahem Salah Abdul-Hamid; Ahmed Elbataa; Mona Mahmoud Elsakka; Anas Mansour; Mostafa Hossam El Din Moawad; Aynur Ozge (PharmaNutrition, 2025)

Petrophysical evaluation and 3D reservoir modeling in Qawasim Formation, El Basant Gas Field, Nile Delta, Egypt: insights from well-log analysis and 2D seismic data - Ahmed Sedki; Mohamed Abd Elkhalek Mahmoud Abdelhady; Hany Elsayed Ahmed; Mohamed Reda (Arabian Journal of Geosciences, 2025)

Physiological, biochemical, apoptosis-linked gene expression, and histopathological insights in Nile catfish subjected to toxicity by magnetite nanogel - Yasmina K. Mahmoud; Shaimaa A. A. Ahmed; Heba H. Mahboub; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Ahmed A. Elnegiry; Sherif M. Shawky; Sahar H. Orabi; Sameh H. Ismail; Simon J. Davies; Mahmoud I. M. Darwish (Fish Physiology and Biochemistry, 2025)

Microbial-priming of seeds with plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi for improving cotton (Gossypium barbadense L.) growth, yield and water productivity under drought stress - Hossam S. El-Beltagi; Essam Abdelaziz El-Waraky; Mohamed M. El-Mogy; Mohamed Fathi El-Nady; Ahmed Mahmoud Ismail; Elsayed B. Belal; Mohammed I. Al-Daej; Nagwa Mohamed El-Khateeb; Lamy Hamed; Metwaly Mahfouz Salem Metwaly (Biologia, 2025)

A novel strategy for enhancing high solid anaerobic digestion of fecal slag and food waste using percolate recirculation and dosage of nano zero-valent iron - Hamza Hassan Yusuf; Pan Xiaofang; Zhi-Long Ye; Taha Abdelfattah Mohammed Abdelwahab; Ahmed Elsayed Mahmoud Fodah (Water Research, 2024)

Valorization of abattoir water discharge through phycoremediation for enhanced biomass and biodiesel production - Mahdy Elsayed; Yevheniia Mysnyk; Mohamed Mahmoud-Aly; Ehab Mostafa; Adel W. Almutairi; Doaa G. Abbas; Mohamed M. Ibrahim; Dieter Hanelt; Abdelfatah Abomohra (Biomass and Bioenergy, 2024)

Genetic determinants of weed control in rice (Oryza sativa L.) using allelopathy approach - Mahmoud E. Selim; Essam E. ELShamey; Neama A. ELkholy; Mohamed Abdelrahman; Elsayed A. Abo-Marzoka; Walid H. Elgamal; Mahmoud A. Elsayed; Kotb A. Attia; Abdel-Halim Ghazy; Hussein Abdel-Haleem (Cereal Research Communications, 2024)

The prevalence, antimicrobial susceptibility, virulence, and antimicrobial resistance genes of multidrug-resistant Vibrio parahaemolyticus recovered from Oreochromis niloticus - Abdelazeem M. Algammal; Mahmoud Mabrok; Khyreyah J. Alfifi; Saad Alghamdi; Enas A. Almanzalawi; Tahani M. Alqahtani; Mahmoud E. Elsayed; Hanan Elghayaty; Zainab Mohamed El Kattawy; Reham M. El-Tarabili (Aquaculture International, 2024)

Using moringa (Moringa oleifera) seed protein hydrolysate as a dietary protein supplement modulates hemato-biochemical indices, antioxidant response, and tissue histo-morphology of Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Shimaa A. Amer; Nasreddin R. Rhouma; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Heba M. Abdel-Ghany; Gehad E. Elshobaky; Mahmoud M. El-Saber; Ali Osman; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Shear behavior of reinforced concrete beams comprising a combination of crumb rubber and rice husk ash - Mahmoud.A.M. Hassanean; Sara.A.M. Hussein; Mahmoud Elsayed (Engineering Structures, 2024)

Effects of Pichia manshurica yeast supplementation on ruminal fermentation, nutrient degradability, and greenhouse gas emissions in aflatoxin B1 contaminated diets - Yosra Soltan; Amr Morsy; Mahmoud Elazab; Amr E. El-Nile; Nesrein Hashem; Mohamed Sultan; Younis Hamad; Gomaa Abo El Lail; Sohila Abo-Sherif; Nassra Dabour; Ehab Kheadr; Elsayed Hafez; et al. (Tropical Animal Health and Production, 2024)
Yeast feed additives present a natural approach for mitigating ruminal greenhouse gases (GHG) in an environmentally sustainable manner. This study aimed to isolate yeast strains from ruminal fluids capable of reducing GHG from Aflatoxin (AFB1) contaminated diets. Two isolates of Pichia manchuria (FFNLYFC1 and FFNLYFC2) were isolated and identified from the ruminal contents of dairy Zaraibi goats. An in vitro gas production assay was conducted to evaluate the impact of the yeast supplementations on a basal diet contaminated with AFB1 or not. The treatments were control (-AFB1; basal diet without supplements), control with AFB1 contamination (+ AFB1; basal diet containing 20 ppb AFB1), and yeast-supplemented diets (basal diet supplemented with Saccharomyces cerevisiae , and three treatments of P. manchuria [FFNLYFC1, FFNLYFC2, and their mixture at 1:1 ratio (Mix)]. High biological components were detected in abundance of both FFNLYFC1, FFNLYFC2 filtrates (e.g., diisooctyl phthalate). The Mix and FFNLYFC2 of P. manchuria reduced ( P < 0.05) methane by 23.5 and 20.8%, respectively, while only Mix inhibited carbon dioxide by 44% compared to the + AFB1 diet. All yeast diets improved ( P < 0.05) ammonia concentration, total protozoal and Entodinium spp. counts compared to + AFB1 diet. The Mix exhibited higher ( P < 0.05) values of ruminal degraded cellulose, total short-chain fatty acids, acetate and propionate compared to the individual isolates diets. The results suggest synergistic interactions among P. manshurica isolates, leading to enhanced ruminal fermentation and reduced GHG emissions while alleviating the adverse effects of AFB1. Therefore, we recommended the Mix of P. Manchuria as a novel feed additive to ruminant diets.

Implementation of a multistage predictive energy management strategy considering electric vehicles using a novel hybrid optimization technique - M.H. Elkholy; Tomonobu Senjyu; Mahmoud M. Gamil; Mohammed Elsayed Lotfy; Dongran Song; Gul Ahmad Ludin; Ahmad Shah Irshad; Taghreed Said (Journal of Cleaner Production, 2024)

Adipose-Derived Mesenchymal Stem Cells and Their Derived Epidermal Progenitor Cells Conditioned Media Ameliorate Skin Aging in Rats - Omar I. Badr; Aya Anter; Ihab Magdy; Marvellous Chukueggu; Moamen Khorshid; Mohamed Darwish; Mohamed Farrag; Menna Elsayed; Youmna Amr; Yomna Amgad; Tasnim Mahmoud; Mohamed M. Kamal (Tissue Engineering and Regenerative Medicine, 2024)

Enhanced upregulation of SIRT1 via pioglitazone and ligustrazine confers protection against ethanol-induced gastric ulcer in rats - Sara A. Mahmoud; Abeer Elkhoely; Elsayed K. El-Sayed; Amany A. E. Ahmed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Gastric ulcer is a disturbing disease that impacts many people worldwide. Pioglitazone (Piog), a thiazolidinedione, and ligustrazine (Ligu), a natural component of Ligusticum chuanxiong possess gastroprotective properties. However, the underlying mechanism is not well elucidated. The present study aimed to investigate the gastroprotective effects of Piog (15 mg/kg, p.o.), Ligu (15 mg/kg, p.o.), and their combination against ethanol-induced gastric ulcer in rats. Omeprazole (10 mg/kg) was used as a standard. Pre-treatment for 7 days with Piog, Ligu, and (Piog+Ligu) effectively alleviated ethanol-predisposed oxidative stress and inflammation through restoring HO-1, GSH, and SOD tissue levels and decreasing elevated MDA, TNF-α, ICAM, I-NOS, and IL-1β contents. Moreover, Piog, Ligu, and (Piog+Ligu) markedly inhibited the ethanol-induced increase of gastric NF-KB and BAX. In contrast, this pre-treatment regimen significantly accelerated protein expression of SIRT1, Nrf2, and Bcl-2, along with autophagic proteins, ATG5 and Beclin. Interestingly, macroscopic, histopathological examination and mucin content were in harmony with previous results, where pre-treatment with Piog, Ligu, and (Piog+Ligu) showed a declined mucosal injury as evidenced by the remarkable decrease of the ulcer area percentage by 62.3%, 38.7%, and 91.2%, respectively, compared to the ethanol-ulcerated group. In conclusion, Piog and Ligu exhibited remarkable gastroprotective properties. Our study was the first to show that Piog, Ligu, and (Piog+Ligu) ameliorated oxidative stress, inflammation, and apoptosis and accelerated the autophagic process via the upregulation of the upstream SIRT1 protein. It is worth mentioning that future studies are needed to pave the way for the clinical use of Piog and Ligu as gastro-protective agents.

Direct evaporative cooling for sustainability and environmental conservation - Hesham Safwat; Mahmoud Ahmed Elsayed; Mahmoud Alghrieb; Iman El – Mahallawi (Innovative Infrastructure Solutions, 2024)

Mesoporous magnetic biochar derived from common reed (Phragmites australis) for rapid and efficient removal of methylene blue from aqueous media - Wael Ibrahim Mortada; Mahmoud Mohsen Ghaith; Nada Elsayed Khedr; Mostafa Ibrahim Ellethy; Alaa Waleed Mohsen; Amira Labib Shafik (Environmental Science and Pollution Research, 2024)
A novel mesoporous magnetic biochar (MBC) was prepared, using a randomly growing plant, i.e., common reed, as an exporter of carbon, and applied for removal of methylene blue (MB) from aqueous solutions. The prepared sorbent was characterized by nitrogen adsorption/desorption isotherm, saturation magnetization, pH of point of zero charges (pH PZC ), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The obtained MBC has a specific surface area of 94.2 m 2 g −1 and a pore radius of 4.1 nm, a pore volume of 0.252 cm 3 g −1 , a saturation magnetization of 0.786 emu g −1 , and a pH PZC of 6.2. Batch adsorption experiments were used to study the impact of the physicochemical factors involved in the adsorption process. The findings revealed that MB removal by MBC was achieved optimally at pH 8.0, sorbent dosage of 1.0 g L −1 , and contact time of 30 min. At these conditions, the maximum adsorption was 353.4 mg g −1 . Furthermore, the adsorption isotherm indicated that the Langmuir pattern matched well with the experimental data, compared to the Freindlich model. The ∆ G was − 6.7, − 7.1, and − 7.5 kJ mol −1 , at 298, 308, and 318 K, respectively, indicating a spontaneous process. The values of ∆ H and ∆ S were 5.71 kJ mol −1 and 41.6 J mol −1 K −1 , respectively, suggesting endothermic and the interaction between MB and MBC is van der Waals type. The absorbent was regenerated and reused for four cycles after elution with 0.1 mol L −1 of HCl. This study concluded that the magnetic biochar generated from common reed has tremendous promise in the practical use of removing MB from wastewater. Graphic Abstract

The Role of RIN3 Gene in Alzheimer’s Disease Pathogenesis: a Comprehensive Review - Mostafa Meshref; Hazem S. Ghaith; Mohamed Ahmed Hammad; Mahmoud Mohamed Mohamed Shalaby; Faris Ayasra; Fatma Ahmed Monib; Mohamed S. Attia; Mahmoud A. Ebada; Hanaa Elsayed; Ali Shalash; Eshak I. Bahbah (Molecular Neurobiology, 2024)
Alzheimer’s disease (AD) is a globally prevalent form of dementia that impacts diverse populations and is characterized by progressive neurodegeneration and impairments in executive memory. Although the exact mechanisms underlying AD pathogenesis remain unclear, it is commonly accepted that the aggregation of misfolded proteins, such as amyloid plaques and neurofibrillary tau tangles, plays a critical role. Additionally, AD is a multifactorial condition influenced by various genetic factors and can manifest as either early-onset AD (EOAD) or late-onset AD (LOAD), each associated with specific gene variants. One gene of particular interest in both EOAD and LOAD is RIN3, a guanine nucleotide exchange factor. This gene plays a multifaceted role in AD pathogenesis. Firstly, upregulation of RIN3 can result in endosomal enlargement and dysfunction, thereby facilitating the accumulation of beta-amyloid (Aβ) peptides in the brain. Secondly, RIN3 has been shown to impact the PICLAM pathway, affecting transcytosis across the blood-brain barrier. Lastly, RIN3 has implications for immune-mediated responses, notably through its influence on the PTK2B gene. This review aims to provide a concise overview of AD and delve into the role of the RIN3 gene in its pathogenesis.

Evaluating the impact of artificial maturation on the petrophysical and geochemical properties of unconventional shale formations by integrating dielectric and NMR measurements - Amjed Hassan; Mahmoud Elsayed; Ali Oshaish; Salah Al-Ofi; Ammar El-Husseiny; Israa S. Abu-Mahfouz; Mohamed Mahmoud; Mohamed Abouelresh; Hussein Attia (International Journal of Coal Geology, 2024)

From diagnosis to resistance: a symphony of miRNAs in pheochromocytoma progression and treatment response - Elsayed G. E. Elsakka; Ahmed Elshafei; Mohamed A. Elkady; Amr Mohamed Yehia; Ahmed I. Abulsoud; Reem K. Shahin; Nourhan M. Abdelmaksoud; Samy Y. Elkhawaga; Ahmed Ismail; Mahmoud Mohamed Mokhtar; Mahmoud A. Elrebehy; Maghawry Hegazy; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Enhancing Growth and Productivity of ‘Anna’ Apple Orchards: Mitigating Abiotic Stresses Through Moringa Leaf Extract and Mannitol Foliar Application at Critical Stages - Thanaa Sh. M. Mahmoud; Farid M. Rohim; Shaimaa I. M. Elsayed; Said A. Saleh (Applied Fruit Science, 2024)

Synthesis of Nano-silica Oxide for Heavy Metal Decontamination from Aqueous Solutions - Naira Meky; Eslam Salama; Mohamed F. Soliman; Soheair G. Naeem; Mona Ossman; Mahmoud Elsayed (Water, Air, & Soil Pollution, 2024)
In the current study, nano-silica oxide (nano-SiO 2 ) was fabricated via the sol-gel technique. Then, the prepared nano-SiO 2 was characterized using X-ray diffractometer (XRD), transmission electron microscopy (TEM) coupled with energy-dispersive X-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and Brunauer-Emmett-Teller (BET) specific surface area analysis. Furthermore, the fabricated nano-SiO 2 was applied for the adsorption of lead Pb (II) and chromium Cr (VI) from aqueous solutions. Additionally, the influence of different operating factors such as contact time (0–180 min), initial pH (1–11), nano-SiO 2 dose (0.1–8 g L −1 ), initial metal ion concentration (5–100 mg L −1 ), and the temperature (30–85 °C) was investigated. The nano-SiO 2 doses of 0.5 and 1 g L −1 were selected as the optimal adsorbent dose for the removal of Pb (II) and Cr (VI), respectively. These doses achieved a removal efficiency of 82.3% and 78.5% for Pb (II) and Cr (VI), after 60 and 90 min, at initial pH values of 5 and 2, respectively, using 10 mg L −1 initial metal concentration, and at room temperature. Lastly, kinetic and equilibrium studies were competently fitted using the pseudo-second-order and Freundlich models, respectively. Adsorption thermodynamic studies designate the spontaneous and thermodynamic nature of the adsorption process. These results reveal the efficiency of the fabricated nano-SiO 2 as an adsorbent for heavy metal removal from aqueous solutions. Graphical Abstract

Isolation and structural characterization of phytoconstituents from leaves of Bignonia binata - Mamdouh Nabil Samy; Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Sachiko Sugimoto; Katsuyoshi Matsunami; Mohamed Salah Kamel (Natural Product Research, 2024)

Recent progress in water decontamination from dyes, pharmaceuticals, and other miscellaneous nonmetallic pollutants by layered double hydroxide materials - Mohamed E. Mahmoud; Rehab M. El-Sharkawy; Elhassan A. Allam; Gehan M. Nabil; Febee R. Louka; Mohamed Abdel Salam; Sarah M. Elsayed (Journal of Water Process Engineering, 2024)

Machado-Joseph disease in a Sudanese family links East Africa to Portuguese families and allows reestimation of ancestral age of the Machado lineage - Sandra Martins; Ashraf Yahia; Inês P. D. Costa; Hassab E. Siddig; Rayan Abubaker; Mahmoud Koko; Marc Corral-Juan; Antoni Matilla-Dueñas; Alexis Brice; Alexandra Durr; Eric Leguern; Laura P. W. Ranum; et al. (Human Genetics, 2023)
Machado-Joseph disease (MJD/SCA3) is the most frequent dominant ataxia worldwide. It is caused by a (CAG) n expansion. MJD has two major ancestral backgrounds: the Machado lineage, found mainly in Portuguese families; and the Joseph lineage, present in all five continents, probably originating in Asia. MJD has been described in a few African and African-American families, but here we report the first diagnosed in Sudan to our knowledge. The proband presented with gait ataxia at age 24; followed by muscle cramps and spasticity, and dysarthria, by age 26; he was wheel-chair bound at 29 years of age. His brother had gait problems from age 20 years and, by age 21, lost the ability to run, showed dysarthria and muscle cramps. To assess the mutational origin of this family, we genotyped 30 SNPs and 7 STRs flanking the ATXN3 _CAG repeat in three siblings and the non-transmitting father. We compared the MJD haplotype segregating in the family with our cohort of MJD families from diverse populations. Unlike all other known families of African origin, the Machado lineage was observed in Sudan, being shared with 86 Portuguese, 2 Spanish and 2 North-American families. The STR-based haplotype of Sudanese patients, however, was distinct, being four steps (2 STR mutations and 2 recombinations) away from the founder haplotype shared by 47 families, all of Portuguese extraction. Based on the phylogenetic network constructed with all MJD families of the Machado lineage, we estimated a common ancestry at 3211 ± 693 years ago.

Neem seed protein hydrolysate as a fishmeal substitute in Nile tilapia: Effects on antioxidant/immune pathway, growth, amino acid transporters-related gene expression, and Aeromonas veronii resistance - Afaf N. Abdel Rahman; Shimaa A. Amer; Shimaa R. Masoud; Mahmoud M. El-Saber; Ali Osman; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Tarek Khamis; Rowida E. Ibrahim (Aquaculture, 2023)

Biphasic lignocellulose fractionation for staged production of cellulose nanofibers and reactive lignin nanospheres: A comparative study on their microstructures and effects as chitosan film reinforcing - Meysam Madadi; Mahdy Elsayed; Guojie Song; Rajeev Kumar; Mohamed Mahmoud-Aly; Bikram Basak; Byong-Hun Jeon; Fubao Sun (Chemical Engineering Journal, 2023)

Correction to: Potentials of mono‑ and multi‑metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)

Potentials of mono- and multi-metal ion removal from water with cotton stalks and date palm stone residuals - Heba Nagy; Manal Fawzy; Elsayed Hafez; Alaa El Din Mahmoud (Environmental Science and Pollution Research, 2023)
In this work, cotton stalks ( Gossypium barbadense ) and date palm stones ( Phoenix dactylifera ) have been used as biosorbents to remove cadmium; Cd(II), lead; Pb(II), and zinc; Zn(II) from mono- and multi-solutions. Each biosorbent was characterized using SEM-EDX, and FT-IR. The findings showed that pH, dose, contact time, metal concentration, and particle size affect the treatment process. The adsorption pattern was Pb(II) > Cd(II) > Zn(II) for both biosorbents. The adsorption performance of cotton stalks was higher than that of date palm stones. The fitted maximum uptake capacities; q m of cotton stalks were higher than those of date palm stones. The maximum adsorption at optimum conditions of Pb(II), Cd(II), and Zn(II) with cotton stalks were 98%, 92.1%, and 78.9%, respectively, within 30 min. While the maximum adsorption of Pb(II), Cd(II), and Zn(II) with date palm stones were 94.6%, 76%, and 68.6%, respectively. Results confirmed the antagonistic effect of heavy metal removal at optimum conditions. Biosorbents could remove ~ 100% of the metal ions from real wastewater samples. Regeneration investigation revealed a successful reusability of both biosorbents for four cycles.

Impact of Streptococcus agalactiae Challenge on Immune Response, Antioxidant Status and Hepatorenal Indices of Nile Tilapia: The Palliative Role of Chitosan White Poplar Nanocapsule - Afaf N. Abdel Rahman; Sameh H. Ismail; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samah S. Khalil; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Simon J. Davies; Rowida E. Ibrahim (Fishes, 2023)
A new insight into the synthesis of the herbal plant (White poplar, Poplus alba) leave extract using chitosan nanocapsule was studied. The in vitro antibacterial activity of chitosan white poplar nanocapsule (CWPNC) against Streptococcus agalactiae (S. agalactiae) was determined. About 120 fish were categorized for 7 days into four groups. The first and second (CWPNC) groups were treated with 0 mg/L and 3 mg/L CWPNC in the water, respectively, without being challenged; the first group was a control. The third (S. agalactiae) and fourth (CWPNC + S. agalactiae) groups were treated with 0 and 3 mg/L CWPNC, respectively, and challenged with S. agalactiae (0.5 × 107 CFU/mL). The obtained results revealed that CWPNC had an in vitro antibacterial activity against S. agalactiae. Moreover, S. agalactiae infection caused a significant elevation (p

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials - Mohamed Sayed Zaazouee; Mahmoud Eleisawy; Amira M. Abdalalaziz; Mahmoud M. Elhady; Omar Adel Ali; Taghreed Mohamed Abdelbari; Sara Mohamed Hasan; Hossam Waleed Almadhoon; Alaa Yehia Ahmed; Alaa Shaban Fassad; Rewan Elgendy; Eman Adnan Abdel-Baset; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19. Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywords/Mesh terms. Only randomized clinical trials (RCTs) that addressed the topic were included. The Cochrane tool was used to assess the studies’ risk of bias, and the data were analyzed using the review manager (RevMan 5.4). We included nine RCTs with 1586 confirmed COVID-19 patients. Vitamin D group showed a significant reduction of intensive care unit (ICU) admission (risk ratio = 0.59, 95% confidence interval (CI) [0.41, 0.84], P = 0.003), and higher change in vitamin D level (standardized mean difference = 2.27, 95% CI [2.08, 2.47], P < 0.00001) compared to the control group. Other studied hospital and laboratory outcomes showed non-significant difference between vitamin D and the control group ( P ≥ 0.05). In conclusion, vitamin D reduced the risk of ICU admission and showed superiority in changing vitamin D level compared to the control group. However, other outcomes showed no difference between the two groups. More RCTs are needed to confirm these results.

Standards of NGS Data Sharing and Analysis in Ataxias: Recommendations by the NGS Working Group of the Ataxia Global Initiative - Danique Beijer; Brent L. Fogel; Sergi Beltran; Matt C. Danzi; Andrea H. Németh; Stephan Züchner; Matthis Synofzik; Astrid Adarmes; Saud Alhusaini; Mahmoud Reza Ashrafi; Luis Bataller; Enrico Bertini; et al. (The Cerebellum, 2023)
The Ataxia Global Initiative (AGI) is a worldwide multi-stakeholder research platform to systematically enhance trial-readiness in degenerative ataxias. The next-generation sequencing (NGS) working group of the AGI aims to improve methods, platforms, and international standards for ataxia NGS analysis and data sharing, ultimately allowing to increase the number of genetically ataxia patients amenable for natural history and treatment trials. Despite extensive implementation of NGS for ataxia patients in clinical and research settings, the diagnostic gap remains sizeable, as approximately 50% of patients with hereditary ataxia remain genetically undiagnosed. One current shortcoming is the fragmentation of patients and NGS datasets on different analysis platforms and databases around the world. The AGI NGS working group in collaboration with the AGI associated research platforms—CAGC, GENESIS, and RD-Connect GPAP—provides clinicians and scientists access to user-friendly and adaptable interfaces to analyze genome-scale patient data. These platforms also foster collaboration within the ataxia community. These efforts and tools have led to the diagnosis of > 500 ataxia patients and the discovery of > 30 novel ataxia genes. Here, the AGI NGS working group presents their consensus recommendations for NGS data sharing initiatives in the ataxia field, focusing on harmonized NGS variant analysis and standardized clinical and metadata collection, combined with collaborative data and analysis tool sharing across platforms.

Clarithromycin-, and metronidazole-resistant Helicobacter pylori isolated from raw and ready-to-eat meat in Mansoura, Egypt - Aya Elsayed Maghrabia; Hend Ali Elshebrawy; Mahmoud Ahmed Mahros; Mohammed Mohammed Elgazzar; Khalid Ibrahim Sallam (International Journal of Food Microbiology, 2023)

How can imported monkeypox break the borders? A rapid systematic review - Ramy Mohamed Ghazy; Elsayed Mohamed Hammad; Mohamed Ashraf Hall; Amira Mahboob; Sally Zeina; Eman H. Elbanna; Noha Fadl; Shaimaa Abdelaziz Abdelmoneim; Rony ElMakhzangy; Hammad Mohamed Hammad; Afrah humidan Suliman; Hayat Hasab Alkreem Atia; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Expression profiling of HSP 70 and interleukins 2, 6 and 12 genes of Barki sheep during summer and winter seasons in two different locations - Raed A. Abu Rawash; Mahmoud A. Sharaby; Gamal El-Din A. Hassan; Alaa E. Elkomy; Elsayed E. Hafez; Salma H. Abu Hafsa; Mohamed M. I. Salem (International Journal of Biometeorology, 2022)
The objectives of this research were to contrast the expression values of heat shock protein (HSP70) and interleukins 2, 6 and 12 (IL 2, IL 6 and IL 12) genes in summer and winter in two different locations in Egypt (Alexandria zone and Matrouh zone) to deduce changes in thermo-physiological traits and biochemical blood metabolites of Barki sheep. A total of 50 ewes (20 in Alexandria and 30 in Matrouh) were individually blood sampled to determine plasma total protein (TP), Albumin, Globulin and Glucose constituents and T3, T4 and cortisol hormones. The thermo-physiological parameters of rectal temperature (RT, °C), skin temperature (ST, °C), Wool temperature (WT, °C), respiration rate (RR, breaths/min) and pulse rate (PR, beats/min) were measured for each ewe. Expressions of IL 2, IL 6, IL 12 and HSP 70 in summer and winter were analyzed along with thermo-physiological parameters and blood biochemical metabolites. In both locations, THI had significant effects on ST, WT, PR and RR, but not significant on RT. However, it had no significant effects on blood plasma metabolites and hormonal concentrations in the two locations in summer and winter. In Alexandria location, THI had negative significant effect on the expressions of IL-2 and IL-6 but positively affected on HSP70 genes in winter, while the expression of IL-12 gene was not affected by seasons, whereas in Matrouh zone, the effects of THI on the expressions of all tolerance genes were not significant. The results of the current study suggest that IL-2, IL-6 and HSP70 genes could be used as molecular markers for heat/cold stress.

Modulating Gliclazide Release and Bioavailability Utilizing Multiparticulate Drug Delivery Systems - Ebtesam W. Elsayed; Ahmed A. El-Ashmawy; Khaled M. Mahmoud; Nadia M. Mursi; Laila H. Emara (Journal of Pharmaceutical Innovation, 2022)

Dietary astaxanthin modulated the performance, gastrointestinal histology, and antioxidant and immune responses and enhanced the resistance of Litopenaeus vannamei against Vibrio harveyi infection - Elsayed A. A. Eldessouki; Amany M. Diab; Talal A. M. Abo Selema; Nader M. Sabry; Mahmoud M. Abotaleb; Riad H. Khalil; Nasser El-Sabbagh; Nehal A. Younis; Mohsen Abdel-Tawwab (Aquaculture International, 2022)
Astaxanthin (AX) is one of the commonly used feed supplements to enhance the growth performance and provide antioxidant and immune functions of several aquatic animals. In the current study, juveniles of white-leg shrimp ( Litopenaeus vannamei ) with mean initial weight of 0.340 ± 0.041 g were fed with diets supplemented with 0 (control), 25, 50, 100, and 200 mg/kg feed for 8 weeks. At the end of the feeding trial, shrimps were exposed to Vibrio harveyi , and their mortality rates were observed for additional 10 days. The growth indices in the AX-fed groups were significantly ( P P P cMn-SOD , CAT , and GPx genes were significantly upregulated in the hepatopancreas of L. vannamei fed with AX-enriched diets (especially in the 200-mg/kg feed treatment) as compared with the control diet. The immunity indices of the AX treatments (hematocyte count, total protein, lysozyme, phagocytic activity, and phenoloxidase) of L. vannamei were linearly ( P P V. harveyi abundance. After the bacterial challenge, feeding L. vannamei with dietary AX significantly increased ( P L. vannamei against V. harveyi infection.

Evaluation of different bacterial honey isolates as probiotics and their efficient roles in cholesterol reduction - Noura O. Abdelsamad; Mona A. Esawy; Zeinab E. Mahmoud; Asmaa I. El-Shazly; Tarek R. Elsayed; Amira A. Gamal (World Journal of Microbiology and Biotechnology, 2022)
Continue to hypothesize that honey is a storehouse of beneficial bacteria, and the majority of these isolates are levansucrase producers. Accordingly, ten bacterial strains were isolated from different honey sources. Four honey isolates that had the highest levansucrase production and levan yield were identified by the partial sequencing of the 16S rRNA gene as Achromobacter sp. (10A), Bacillus paralicheniformis (2M), Bacillus subtilis (9A), and Bacillus paranthracis (13M). The cytotoxicity of the selected isolates showed negative blood hemolysis. Also, they are sensitive to the tested antibiotics (Amoxicillin + Flucloxacillin, Ampicillin, Gentamicin, Benzathine benzylpenicillin, Epicephin, Vancomycin, Amikacin, and Zinol). The isolates had strong alkaline stability (pHs 9, 11) and were resistant to severe acidic conditions (29–100 percent). The tested isolates recorded complete tolerance to both H 2 O 2 and the bile salt (0.3% Oxgall powder) after 24 h incubation. The cell-free supernatant of the examined strains had antifungal activities against C. Albicans with varying degrees. Also, isolates 2M and 13M showed strong activities against S. aureus . The isolates showed strong adhesion and auto-aggregation capacity. Isolate 10A showed the highest antioxidant activity (91.45%) followed by 2M (47.37%). The isolates recorded different catalase and protease activity. All isolates produced cholesterol oxidase and lipase with different levels. Besides, the four isolates reduced LDL (low-density lipoprotein) to different significant values. The cholesterol-reducing ability varied not only for strains but also for the time of incubation. The previous results recommended these isolates be used safely in solving the LDL problem.

The optimized inclusion level of Bacillus subtilis fermented Azolla pinnata in Nile tilapia (Oreochromis niloticus) diets: immunity, antioxidative status, intestinal digestive enzymes and histomorphometry, and disease resistance - Taha Ismail; Elsayed Hegazi; Eldsokey Nassef; Ola A. Habotta; Mahmoud S. Gewaily (Fish Physiology and Biochemistry, 2022)
A 95-day feeding trial was conducted to evaluate the outcomes of feeding Bacillus subtilis fermented Azolla ( BSFA ) on nonspecific immunity, antioxidative status, intestinal digestive enzymes and histomorphometry, and disease resistance in the Nile tilapia. We formulated five isonitrogenous and isocaloric experimental diets to incorporate BSFA at level of (0%, 15%, 30%, 45%, 60%). The growth performance parameters (FBW, BWG, SGR, PER, and FCR) revealed a significant increase in the BSFA30 tilapia group compared to the control group followed by BSFA45 ( P < 0.05). The BSFA30 group exhibited the highest nonspecific immunity parameters including (lysozyme activity, phagocytic index, and phagocytic activity) compared to other groups ( P < 0.05). SOD and GPx reported the highest values in the BSFA60 group. Nile tilapia carcass composition was not influenced by BSFA inclusion level ( P > 0.05). Interestingly, Nile tilapia fed with BSFA15 diet exhibited the highest protease activity level ( P < 0.05), while those fed on BSFA30 documented the highest amylase activity. Intestinal histomorphology was significantly enhanced with the gradual increase of administrated BSFA . Regarding the tilapia disease resistance against Aeromonas septicemia , BSFA significantly diminished the cumulative mortality compared to the control group. To sum up, BSFA was more effective in improving the growth performance and immunity of Nile tilapia. Graphical abstract

Model Synthetic Samples for Validation of NMR Signal Simulations - Nicholas N. A. Ling; Syed Rizwanullah Hussaini; Mahmoud Elsayed; Paul R. J. Connolly; Ammar El-Husseiny; Mohamed Mahmoud; Eric F. May; Michael L. Johns (Transport in Porous Media, 2022)
Simulations of nuclear magnetic resonance (NMR) signal from fluids contained in porous media (such as rock cores) need to account for both enhanced surface relaxation and the presence of internal magnetic field gradients due to magnetic susceptibility contrast between the rock matrix and the contained fluid phase. Such simulations are typically focussed on the extraction of the NMR T 2 relaxation distribution which can be related to pore size and indirectly to system permeability. Discrepancies between such NMR signal simulations on digital rock cores and associated experimental measurements are however frequently reported; these are generally attributed to spatial variations in rock matric composition resulting in heterogeneously distributed NMR surface relaxivities (ρ) and internal magnetic field gradients. To this end, a range of synthetic sediments composed of variable mixtures of quartz and garnet sands were studied. These two constituents were selected for the following reasons: they have different densities allowing for ready phase differentiation in 3D μCT images of samples to use as simulation lattices and they have distinctly different ρ and magnetic susceptibility values which allow for a rigorous test of NMR simulations. Here these 3D simulations were used to calculate the distribution of internal magnetic field gradients in the range of samples, these data were then compared against corresponding NMR experimental measurements. Agreement was reasonably good with the largest discrepancy being the simulation predicting weak internal gradients (in the vicinity of the quartz sand for mixed samples) which were not detected experimentally. The suite of 3D μCT images and associated experimental NMR measurements are all publicly available for the development and validation of NMR simulation efforts.

LC-MS-based identification of bioactive compounds and hepatoprotective and nephroprotective activities of Bignonia binata leaves against carbon tetrachloride-induced injury in rats - Mamdouh Nabil Samy; Ashraf Nageeb Elsayed Hamed; Basma Khalaf Mahmoud; Eman Zekry Attia; Usama Ramadan Abdelmohsen; Michael Atef Fawzy; Mina Ezzat Attya; Mohamed Salah Kamel (Natural Product Research, 2022)

Virulence analysis of wheat powdery mildew races during 2019–2020 seasons in Egypt - Moustafa Mahmoud El-Shamy; Mona Elsayed Mohamed (Cereal Research Communications, 2022)

Metabolomic profiling and biological investigation of Tabebuia Aurea (Silva Manso) leaves, family Bignoniaceae - Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Mamdouh Nabil Samy; Usama Ramadan Abdelmohsen; Eman Zekry Attia; Michael Atef Fawzy; Rana Hosny Refaey; Mohammad Alaraby Salem; Sheila Marie Pimentel-Elardo; Justin R. Nodwell; Samar Yehia Desoukey; Mohamed Salah Kamel (Natural Product Research, 2021)

Assessment of polyethylene/Zn-ionic as a diesel fuel sulfur adsorbent: gamma radiation effect and response surface methodology - Elsayed Gamal Zaki; Dina Mohmed; Modather Farouk Hussein; Mai Mahmoud El-Zayat; Fathi Samir Soliman; Delvin Aman (Environmental Science and Pollution Research, 2021)

Selenium Nanoparticles Act Potentially on the Growth Performance, Hemato-Biochemical Indices, Antioxidative, and Immune-Related Genes of European Seabass (Dicentrarchus labrax) - Marwa F. Abd El-Kader; Ahmed F. Fath El-Bab; Mohamed F. Abd-Elghany; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Mahmoud A. O. Dawood (Biological Trace Element Research, 2021)

Formulation, Pharmacokinetics evaluation, and IVIVC Assessment of Gliclazide Multiparticulates in Rat Model - Ahmed A. El-Ashmawy; Aya R. Abdou; Nesrin F. Taha; Ebtesam W. Elsayed; Khaled M. Mahmoud; Laila H. Emara (AAPS PharmSciTech, 2021)

Studies on Microwave-Assisted Pyrolysis of Rice Straw Using Solar Photovoltaic Power - Ahmed Elsayed Mahmoud Fodah; Manoj Kumar Ghosal; Debaraj Behera (BioEnergy Research, 2021)

The utility of electrocardiography and echocardiography in copper deficiency-induced cardiac damage in goats - Ahmed S. Mandour; Roushdy F. Elsayed; Asmaa O. Ali; Ahmed E. Mahmoud; Haney Samir; Amina A. Dessouki; Katsuhiro Matsuura; Izumi Watanabe; Kazuaki Sasaki; Salim Al-Rejaie; Tomohiko Yoshida; Kazumi Shimada; et al. (Environmental Science and Pollution Research, 2021)

Response Surface Methodology as a Useful Tool for Development and Optimization of Sustained Release Ketorolac Tromethamine Niosomal Organogels - Mahmoud M. A. Elsayed; Saleh Abd El Rasoul; Abd El hakim Ramadan; Amal K. Hussein (Journal of Pharmaceutical Innovation, 2020)

Study of the gut Microbiome Profile in Children with Autism Spectrum Disorder: a Single Tertiary Hospital Experience - Shwikar AbdelSalam Ahmed; Azza Mahmoud Elhefnawy; Hanan Galal Azouz; Yara Safwat Roshdy; Mona Hamdy Ashry; Ahmed Elsayed Ibrahim; Marwa Ahmed Meheissen (Journal of Molecular Neuroscience, 2020)

Quantitative Tortuosity Measurements of Carbonate Rocks Using Pulsed Field Gradient NMR - Kaishuo Yang; Ming Li; Nicholas N. A. Ling; Eric F. May; Paul R. J. Connolly; Lionel Esteban; Michael B. Clennell; Mohamed Mahmoud; Ammar El-Husseiny; Abdulrauf R. Adebayo; Mahmoud Mohamed Elsayed; Michael L. Johns (Transport in Porous Media, 2019)

Efficient removal of Cd (II) from contaminated water and soils using nanoparticles from nitrogen fertilizer industry waste - Elsayed Elkhatib; Ahmed Mahdy; Ayman Mahmoud; Mohamed Moharem (Journal of Environmental Health Science and Engineering, 2019)

Numerical Analysis of Sandwich Composite Deep Submarine Pressure Hull Considering Failure Criteria - Mahmoud Helal; Huinan Huang; Defu Wang; Elsayed Fathallah (Journal of Marine Science and Engineering, 2019)
The pressure hull is the primary element of submarine, which withstands diving pressure and provides essential capacity for electronic systems and buoyancy. This study presents a numerical analysis and design optimization of sandwich composite deep submarine pressure hull using finite element modeling technique. This study aims to minimize buoyancy factor and maximize deck area and buckling strength factors. The collapse depth is taken as a base in the pressure hull design. The pressure hull has been analyzed using two composite materials, T700/Epoxy and B(4)5505/Epoxy, to form the upper and lower faces of the sandwich composite deep submarine pressure hull. The laminated control surface is optimized for the first ply failure index (FI) considering both Tsai–Wu and maximum stress failure criteria. The results obtained emphasize an important fact that the presence of core layer in sandwich composite pressure hull is not always more efficient. The use of sandwich in the design of composite deep submarine pressure hull at extreme depths is not a safe option. Additionally, the core thickness plays a minor role in the design of composite deep submarine pressure hull. The outcome of an optimization at extreme depths illustrates that the upper and lower faces become thicker and the core thickness becomes thinner. However, at shallow-to-moderate depths, it is recommended to use sandwich composite with a thick core to resist the shell buckling of composite submarine pressure hull.

New insight into poly (3-hydroxybutyrate) production by Azomonas macrocytogenes isolate KC685000: large scale production, kinetic modeling, recovery and characterization - Noha S. Elsayed; Khaled M. Aboshanab; Mahmoud A. Yassien; Nadia H. Hassouna (Molecular Biology Reports, 2019)

Identification of serum N-glycoproteins as a biological correlate underlying chronic stress response in mice - Motamed Elsayed Mahmoud; Ibrahim F. Rehan; Kh. El-Dawy Ahmed; Amany Abdelrahman; Saeed Mohammadi; Ahmed F. Abou-Elnaga; Mohammed Youssef; Hassan Mahmoud Diab; Doaa Salman; Asmaa Elnagar; Hesham H Mohammed; Obeid Shanab; et al. (Molecular Biology Reports, 2019)

Plantago squarrosa Murray extracts inhibit the growth of some bacterial triggers of autoimmune diseases: GC–MS analysis of an inhibitory extract - Elsayed Omer; Abdelsamed I. Elshamy; Mahmoud Nassar; Joseph Shalom; Alan White; Ian E. Cock (Inflammopharmacology, 2019)

Comparative therapeutic effect of steroidal and non-steroidal anti-inflammatory drugs on pro-inflammatory cytokine production in water buffalo calves (Bubalus bubalis) naturally infected with bronchopneumonia: a randomized clinical trial - Mohamed Abdo Rizk; Motamed Elsayed Mahmoud; Shimaa Abd El-Salam El-Sayed; Doaa Salman (Tropical Animal Health and Production, 2017)

Evaluating interspecific wheat hybrids based on heat and drought stress tolerance - Mohamed I. Hassan; Elsayed A. Mohamed; Mahmoud A. El-rawy; Karam A. Amein (Journal of Crop Science and Biotechnology, 2016)

Cytotoxic ceramides from the Red Sea sponge Spheciospongia vagabunda - Enas Elsayed Eltamany; Amany K. Ibrahim; Mohamed M. Radwan; Mahmoud A. ElSohly; Hashim A. Hassanean; Safwat A. Ahmed (Medicinal Chemistry Research, 2015)

Integrated geologic and geophysical studies of north unstable shelf seismicity, Egypt - Elsayed Fergany; Mahmoud Mekkawi; Maha Abdel Azeem; Ahmed Khalil (Arabian Journal of Geosciences, 2015)

Investigation of a relation between radiogenic heat production and kinetic surface temperature from multispectral ASTER-TIR data: a case study on Elmissikat-Eleridiya granites, Central Eastern Desert, Egypt - Mahmoud Elsaid; Hatem Aboelkhair; Ahmed Dardier; Elsayed Hermas (Arabian Journal of Geosciences, 2014)

Detection of New Point Mutations of BRCA1 and BRCA2 in Breast Cancer Patients - Moufida Bensam; Elsayed Hafez; Doaa Awad; Muhammad El-Saadani; Mahmoud Balbaa (Biochemical Genetics, 2014)

Synthesis and characterization of some chelating polymers bearing maleic acid and/or sodium maleate moieties for removal of some toxic heavy metal ions - Mahmoud Abd El-Ghaffar; Noha Elhalawany; Elsayed Ahmed; Magdy Sabaa (Clean Technologies and Environmental Policy, 2013)

Structure-based predictive model for some benzimidazole inhibitors of hepatitis C virus NS5B polymerase - Amr H. Mahmoud; Mohamed S. A. Elsayed; Mahmoud ElHefnawi (Medicinal Chemistry Research, 2013)

Phytochemical screening of Nepeta cataria extracts and their in vitro inhibitory effects on free radicals and carbohydrate-metabolising enzymes - Abdel Moneam Mohamed Naguib; Mohamed Elsayed Ebrahim; Hanan Farouk Aly; Hemaia Mohamed Metawaa; Ahlam Hosni Mahmoud; Ebtissam A. Mahmoud; Faten Mohamed Ebrahim (Natural Product Research, 2012)

Inhibition of melanogenesis by the extract from Agaricus blazei without affecting iNOS gene expression - Motamed Elsayed Mahmoud; Abd El-Latif Hesham; Yasser Abdel-Galil Ahmed; Mohammed Sayed (World Journal of Microbiology and Biotechnology, 2010)

Extract from Calotropis procera latex activates murine macrophages - Abdel latif Shaker Seddek; Motamed Elsayed Mahmoud; Takahiko Shiina; Haruko Hirayama; Momoe Iwami; Seiji Miyazawa; Hideki Nikami; Tadashi Takewaki; Yasutake Shimizu (Journal of Natural Medicines, 2009)